0.16666666666(12-6x)=5(x+4)

Simple and best practice solution for 0.16666666666(12-6x)=5(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.16666666666(12-6x)=5(x+4) equation:


Simplifying
0.16666666666(12 + -6x) = 5(x + 4)
(12 * 0.16666666666 + -6x * 0.16666666666) = 5(x + 4)
(2 + -1x) = 5(x + 4)

Reorder the terms:
2 + -1x = 5(4 + x)
2 + -1x = (4 * 5 + x * 5)
2 + -1x = (20 + 5x)

Solving
2 + -1x = 20 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
2 + -1x + -5x = 20 + 5x + -5x

Combine like terms: -1x + -5x = -6x
2 + -6x = 20 + 5x + -5x

Combine like terms: 5x + -5x = 0
2 + -6x = 20 + 0
2 + -6x = 20

Add '-2' to each side of the equation.
2 + -2 + -6x = 20 + -2

Combine like terms: 2 + -2 = 0
0 + -6x = 20 + -2
-6x = 20 + -2

Combine like terms: 20 + -2 = 18
-6x = 18

Divide each side by '-6'.
x = -3

Simplifying
x = -3

See similar equations:

| 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 | | 175+g=118 | | 4y=3(y-5)-2 | | 4(24)=4(20+4(4)) | | 4=0.25(w-4/3) |

Equations solver categories